Conformations of flanking bases in HIV-1 RNA DIS kissing complexes studied by molecular dynamics - Réblová, Kamila; Fadrná, Eva; Sarzynska, Joanna; Kulinski, Tadeusz; Kulhánek, Petr; Ennifar, Eric; Koca, Jaroslav; Sponer, Jirí (Biophysical journal, 2007)
Explicit solvent molecular dynamics simulations (in total almost 800 ns including locally enhanced sampling runs) were applied with different ion conditions and with two force fields (AMBER and CHARMM) to characterize typical geometries adopted by the flanking bases in the RNA kissing-loop complexes. We focus on flanking base positions in multiple x-ray and NMR structures of HIV-1 DIS kissing complexes and kissing complex from the large ribosomal subunit of Haloarcula marismortui. An initial x-ray open conformation of bulged-out bases in HIV-1 DIS complexes, affected by crystal packing, tends to convert to a closed conformation formed by consecutive stretch of four stacked purine bases. This is in agreement with those recent crystals where the packing is essentially avoided. We also observed variants of the closed conformation with three stacked bases, while nonnegligible populations of stacked geometries with bulged-in bases were detected, too. The simulation results reconcile differences in positions of the flanking bases observed in x-ray and NMR studies. Our results suggest that bulged-out geometries are somewhat more preferred, which is in accord with recent experiments showing that they may mediate tertiary contacts in biomolecular assemblies or allow binding of aminoglycoside antibiotics.
Keywords: RNA, Viral; Transcription Initiation Site; RNA virová; Nucleic Acid Conformation; HIV-1; vazebná místa; Models, Chemical; Computer Simulation; párování bází; Base Pairing; molekulární modely; Models, Molecular; Binding Sites; konformace nukleové kyseliny; počátek transkripce; dimerizace; počítačová simulace; Dimerization; chemické modely